Prispevek k poznavanju smrtnosti ptic na cestah v Sloveniji - Rubinič, Borut (Acrocephalus, 2001)
The article presents the results of the survey of run over birds registered between January and October 1993 on different Slovene roads. The 513 found cadavers belonged to 57 species: 13 to non-passerines (34 cadavers or 6.6%) and 44 passerines (479 cadavers or 93.4%). The largest share of the run over birds went to the species of urban environments and the species considered very common and common breeders in Slovenia. The eudominant species were HouseSparrow Passer domesticus (35.0%) and Blackbird Turdus merula (18.5%). The species whose abundance was merely 0.2-0.4% were marked as accidentals, and they reached no less than 57.9% of all registered species. The authors believe that the species structure of run over birds changes during the years mainly at the expense of accidentals. During the second part of the survey, i.e. from June to October, a somewhat higher mortality rate (4.45 cadavers perday) was recorded than during the first five months of the year (3.73 cadavers per day), which can be ascribed to the higher share of the young in this particular period. The largest share of the run over young birds was recorded in August (47.4%), although compared with the first half of the year (0.05 cadaver per day) it was much greater in the second part of the year (1.21 cadaver per day).
Keywords: Age factors; Birds; ceste; Classification; Letni časi; mortaliteta; Motor vehicles; Motorna vozila; Ptice; Seasons; Starostni faktorji; Transport; Transportation